Peristomal Dermatitis: Treatment with Green Banana Peel (Musa sapientum) Powder - da Silva, Ana Cristina; Simões, Isabella Stephanie; Salomé, Geraldo Magela; Atzingen, Dênia Amélia Novato Castelli von; Mendonça, Adriana Rodrigues dos Anjos (Journal of Coloproctology, 2021)
Objective To develop green banana peel (Musa sapientum) powder for the treatment of peristomal dermatitis, and to evaluate its effectiveness and healing time.Methods A clinical, analytical and longitudinal study. In total, 44 volunteers of both genders, aged > 18 years, with intestinal ostomy, who presented peristomal dermatitis, participated in the research. The sample was divided into two groups: the study group used a powder containing 10% of green banana peel, and the control group used ostomy powder. The research was approved by the Ethics in Research Committees (Comitês de Ética em Pesquisa, CEP, in Portuguese) under opinion n° 2.381.904.Results The healing time of the study group was shorter than that of the control group (p = 0.022). To analyze the results, we used the two-sample t-test (mean days until healing for both study groups).Conclusion The powder containing 10% of green banana peel was developed, and effective healing of the peristomal dermatitis was observed. Compared to the ostomy powder, it presented a shorter healing time.
Keywords: ostomy; phytotherapeutic; irritating dermatitis